Effects of different low temperatures on postharvest physiology and storage quality in Youhou sweet persimmon - JIAO Xuan; ZHANG Huihui; REN Huihui; FENG Zhihong; GAO Zhenfeng; SHI Junfeng; WANG Rufu; ZHANG Lixin (Guoshu xuebao, 2025)
[Objective] Cold storage is an effective way to extend the storage time for fruits, but inappropriate low temperature could accelerate the occurrence of chilling injury (CI) to cold-sensitive fruits, like sweet persimmons. The objective of this study was to investigate the storage characteristics of Youhou sweet persimmon and confirm the appropriate cold storage temperature. [Methods] Fruits of Youhou sweet persimmon (Diospyros kaki L. cv. Youhou) were harvested from an commercial orchard with no visible diseases, insects, and mechanical injuries, and then transported to the laboratory immediately. The experiment fruits were selected afterwards with uniform size, color and maturity. Room temperature (20 ℃, as control) and low temperature conditions (0 ℃, 5 ℃, 10 ℃, and 15 ℃) were employed to store the sweet persimmons. For each treatment, 500 fruits were randomly selected, and three replicates were set. Every 10 kg of fruits were placed into a plastic turnaround box lined with 0.02 mm thick polyethylene package. After 12 hours of precooling, the packages were sealed and stored at different storage temperatures with relative humidity above 95% for 30 days. During storage, 30 fruits were randomly sampled from each treatment every 3 days to determine ethylene production, respiration rate, juice yield, firmness, soluble solid content (SSC), color parameters, and electrolyte leakage. Meanwhile, the flesh tissue was frozen in liquid nitrogen and stored at -80 ℃ for subsequent measurements of malondialdehyde (MDA), H2O2, and antioxidant nutrient contents including total phenolics, total flavonoids, and ascorbic acid. Additionally, 30 fruits were transferred every 3 days from the storage environment to room temperature (20 ℃) for 5 days to evaluate the CI index. [Results] Except for 20 ℃, CI occurred in fruits during cold storage at 0-15 ℃. In detail, the fruits stored at 5 ℃ and 10 ℃ suffered the most severe CI with short periods of 9 d and 15 d in safe storage, respectively. The fruit stored at 15 ℃ had a lower CI index with a safe storage period of 21 d. Furthermore, 0 ℃ slowed distinctly down the occurrence of CI with a prolonged safe storage period of 27 d, and the fruit only showed slight symptom at the end of storage. Compared to 20 ℃, 5 ℃, 10 ℃, and 15 ℃ treatments all exacerbated the fruit quality deterioration. At the end of storage, the fruits stored at 5-15 ℃ had lower degree of firmness, juice yield, H* value, total phenolics, total flavonoids, ascorbic acid and higher degree of L* value, a* value, electrolyte leakage, MDA, H2O2 than the control with significant differences (p<0.05). Moreover, 5 ℃- stored fruits significantly accumulated higher contents of electrolyte leakage, MDA and H2O2 than those in other treatments (p<0.05), leading to a severe disruption of plasma membrane stability, which was associated with the its highest degree of flesh and peel browning (manifesting as the lowest L* value) (p<0.05). In addition, 5 ℃ temperature noticeably accelerated the loss of juice yield (indicating flesh gelation) and antioxidant compounds (p<0.05). 10 ℃ and 15 ℃ temperatures advanced the fruit respiration peak, which was related to the process of maturation and senescence. As a result, the flesh softening and peel color variation were accelerated in fruits stored at above two temperatures, and 10 ℃ was more effective than 15 ℃. At the end of storage, the fruit firmness and SSC content in 10 ℃ group were significantly lower than those of other temperature treatments (p<0.05), and the highest a* value and lower H* values than 5 ℃, 15 ℃, and 20 ℃ in the peel (represented the advanced stages of fruit maturation) were also observed (p<0.05). Similar to 5 ℃, 10 ℃ and 15 ℃ temperatures decreased the juice yield, plasma membrane stability, and antioxidant compounds contents, and the decline levels of 10 ℃ group were significantly greater than 15 ℃ at the end of storage (p<0.05). Under the chilling stress condition, the fruit in 5 ℃ and 10 ℃ group endured higher oxidative pressure, which promoted the consumption of antioxidant compounds. At the end of storage, the fruit stored at 5 ℃ had the lowest contents of total phenolics and ascorbic acid (p<0.05), and the total flavonoids content experienced the greatest loss in the fruit of 10 ℃ group with significant differences from other temperatures (p<0.05), but not with 5 ℃ (p>0.05). Unlike other low temperatures, 0 ℃ obviously alleviated the decline in the quality of sweet persimmons compared to 20 ℃. 0 ℃ significantly inhibited the respiration rate and ethylene production of fruits, leading to delayed process of maturation and senescence, and slowed down the color change of peel, and higher degree of firmness and soluble solids content (p<0.05). It also distinctly reduced the H2O2 accumulation and MDA content (p<0.05), which contributed to integrate the plasma membrane, and maintained higher content of total phenolics, total flavonoids, and ascorbic acid (p<0.05). [Conclusion] 0 ℃ was an appropriate cold storage temperature for sweet persimmons. 5 ℃ and 10 ℃ were the main CI temperatures with different primary CI symptoms, 5 ℃ exhibited flesh browning and gelation, while 10 ℃ accelerated maturation and softening. The results of this study will provide a theoretical basis for the storage and preservation of sweet persimmons.